The Health Level of Sharia Banks: The RGEC Method Approach - Diana, Ni'mah; Suhadi, Suhadi; Hardiningsih, Pancawati (MALIA: Journal of Islamic Banking and Finance, 2024)
Abstract  : This study aims to analyze the influence of bank health using the RGEC method with independent variables of non-performing financing, financing to deposit ratio, good corporate governance, return on assets, operating expenses, operating income, and capital adequacy ratio, on profit growth in banking companies incorporated in Indonesian Sharia Commercial Bank for the period 2020-2022. The research method used is a quantitative approach that uses secondary data obtained through the official website of the Financial Services Authority and the official website of the banking company. There were 11 samples of banking companies selected using purposive sampling. Data analysis using panel data regression through the Eviews 12 program. The results of the study partially showed that non-performing financing, financing to deposit ratio, good corporate governance, and capital adequacy ratio had no effect on profit growth. On the other hand, return on assets has a positive effect and operating expenses have a negative effect on profit growth.